2016
DOI: 10.1136/thoraxjnl-2016-209333.121
|View full text |Cite
|
Sign up to set email alerts
|

S115 Hot-hmv uk trial secondary outcome analysis: early readmission is reduced by the addition of home mechanical ventilation to home oxygen therapy in copd patients with chronic respiratory failure following a life-threatening exacerbation

Abstract: IntroductionHospital readmission following treatment for a life-threatening exacerbation of COPD with acute NIV is frequent and associated with an adverse impact in terms of lung function and health related quality of life. They have been identified as a priority area in the NHS with financial penalties for any patient readmitted within 28 days following discharge.MethodA multicentre open labelled randomised controlled trial recruited patients with persistent hypercapnia (PaCO2 > 7 kPa) 2–4 weeks following res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This trend may continue in the future with the use of ventilators with more sophisticated modes designed to deliver a preset volume within physician prescribed pressure limits; such devices have been evaluated in acute COPD 60 , obesity 61 and mixed patient populations 62 Hence it seems that patients most likely to benefit from NIV are those who require NIV for an inpatient hypercapnic COPD exacerbation and who remain hypercapnic while convalescent 65 . Going forward it is well established that physical frailty is a good marker of the likelihood of readmission 66;67 , and it may be that patient selection for future trial could also profit by including a measure of physical function and/or combining NIV with a rehabilitation program 68 .…”
Section: Niv In Copdmentioning
confidence: 99%
“…This trend may continue in the future with the use of ventilators with more sophisticated modes designed to deliver a preset volume within physician prescribed pressure limits; such devices have been evaluated in acute COPD 60 , obesity 61 and mixed patient populations 62 Hence it seems that patients most likely to benefit from NIV are those who require NIV for an inpatient hypercapnic COPD exacerbation and who remain hypercapnic while convalescent 65 . Going forward it is well established that physical frailty is a good marker of the likelihood of readmission 66;67 , and it may be that patient selection for future trial could also profit by including a measure of physical function and/or combining NIV with a rehabilitation program 68 .…”
Section: Niv In Copdmentioning
confidence: 99%
“…In a randomised study likely to change clinical practice, Murphy et al 66 found that patients with persistent hypercapnia (PaCO 2 >7 kPa) following discharge treated with combined HMV/HOT had fewer 28-day re-admissions and a significant reduction in 12-month exacerbation rate compared with HOT alone. Dr Morris (Manchester) reviewed end-of-life planning in relation to community oxygen prescribing, and found that although median survival was low at around 6 months, only 33% had discussed a DNACPR (‘Do not attempt cardiopulmonary Resuscitation’) decision prior to death 67.…”
Section: Introductionmentioning
confidence: 99%